2006
DOI: 10.1002/pros.20490
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative multi-gene expression profiling of primary prostate cancer

Abstract: The transcript marker PCA3 is a powerful predictor of primary PCa but the inclusion of EZH2, prostein, and TRPM8 adds even more to the diagnostic power. The finding of a significantly higher mRNA expression of three different genes (prostein, PSA, TRPM8) in organ-confined tumors compared to non-organ-confined tumors as well as the multi-marker PCa prediction model developed in the retrospective model system on prostatectomies could be of clinical importance for diagnostic purposes, and should be verified in di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
84
0
2

Year Published

2007
2007
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(94 citation statements)
references
References 51 publications
8
84
0
2
Order By: Relevance
“…There is a general consensus that EZH2 overexpression aggravates during prostate cancer progression. In metastases, even gene amplification is found and associated with strong overexpression, 42 whereas the increases in primary cases are usually moderate, 24,40,44 as in the present study, or are even undetectable. 25 However, the moderate increases in nonmetastatic cancers might be difficult to detect by the RNA-in-situ-hybridization technique used in ref.…”
Section: © 2 0 0 8 L a N D E S B I O S C I E N C E D O N O T D I S supporting
confidence: 70%
See 2 more Smart Citations
“…There is a general consensus that EZH2 overexpression aggravates during prostate cancer progression. In metastases, even gene amplification is found and associated with strong overexpression, 42 whereas the increases in primary cases are usually moderate, 24,40,44 as in the present study, or are even undetectable. 25 However, the moderate increases in nonmetastatic cancers might be difficult to detect by the RNA-in-situ-hybridization technique used in ref.…”
Section: © 2 0 0 8 L a N D E S B I O S C I E N C E D O N O T D I S supporting
confidence: 70%
“…Turning-point values for the specific genes were related to those for TBP, the most stable housekeeping gene in prostate cancer. 44 Immunohistochemistry. For EZH2, DNMT1 and DNMT3B stainings paraffin sections were treated with xylene and ethanol.…”
Section: Patients Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study on nine prostate-related transcripts, PCA3 was found as the best single marker for the detection of prostate carcinoma. 17 Using laser microdissection, Thelen et al 18 detected PCA3 RNA by RT-PCR in all analyzed On a large cohort of 517 patients, Fradet et al 23 demonstrated that uPM3, a test detecting PCA3 and PSA mRNA in urine samples, can be a useful adjunct to current methods for the detection of early prostate cancer. The overall sensitivity and specificity were 66 and 89%, respectively; the positive predictive value was 75% and the negative predictive value was 84%.…”
Section: Discussionmentioning
confidence: 99%
“…Most importantly, it does not ignore the heterogeneity of CaP and can detect prostate cancer more accurately than single marker tests. 70,71 Recent studies have characterized the clonality and heterogeneity of TMPRSS2/ERG fusion in multifocal CaP. 57,72 Both interfocal heterogeneity and intrafocal homogeneity for TMPRSS2/ERG fusion have been found in multifocal CaP in the radical prostatectomy specimens.…”
Section: Multiplex Analysis Of Urine Markers and Future Directionsmentioning
confidence: 99%